Single lung transplantation for adult respiratory distress syndrome after paraquat poisoning. Issue 7 (1st July 1998) - Licker, Marc; Schweizer, Alexandre; Hohn, Laurent; Morel, Denis R; Spiliopoulos, Anastase
Abstract : Ventilator-dependent patients are considered poor candidates for lung transplantation. A 17 year old boy developed adult respiratory distress syndrome (ARDS) due to paraquat poisoning. A single lung transplantation was carried out with a successful outcome.